AUTOMATED CONTROL OF A COGENERATION PLANT USING UNCERTIFIED TYPES OF GASEOUS FUEL - Тарахтій, Ольга; Жуковський, Владислав; Іванеєв, Андрій; Яворський, Олександр; Шувалов, Даниил (SWorldJournal, 2023)
This paper analyzes the existing automatic control systems for cogeneration power plants, studies the properties of a cogeneration plant in the presence of internal and external disturbances in terms of their impact on the electric and thermal power of th